Ineffective risk-reward learning in schizophrenia. (November 2020) - Boka, Emeka; Pozzo, Jill Del; Goetz, Deborah; Remsen, Brooke; Walsh-Messinger, Julie; Getz, Mara; Antonius, Daniel; Malaspina, Dolores
Highlights: Poor decision-making in schizophrenia may reflect risky or inhibited behaviors. Balloon Analogue Risk Task compared risky behavior in schizophrenia versus controls. Healthy participants improved their performance over three successive trials. Schizophrenia group showed no learning effects and had less risk-taking behavior. Suboptimally balanced risk and reward, making them more vulnerable to poor choices. Abstract: The underpinnings of poor decision-making in schizophrenia could reflect excessively risky or inhibited behaviors. This study employed the Balloon Analogue Risk Task (BART) to compare decision-making in schizophrenia cases to that of healthy controls. Individuals with schizophrenia performed significantly differently across three trials, failing to improve their performance as shown by the control group. In the control group, cognitive ability, measured with the Wechsler Adult Intelligence Scale (WAIS-III) showed that Perceptual Organization scores predicted Average Inflations per Trial, Total Balloon Pops, and Total Earnings. Although the schizophrenia cases failed to learn, group performance on the BART was not associated with cognitive ability, but regression analyses showed 41.4% of average inflations per trial were explained by Excitement, Delusions, Emotional Withdrawal, and Poor Rapport; total balloon pops were only explained by emotional withdrawal and Total Earnings were reduced by Delusions, Excitement and Poor Rapport. Only healthy participants demonstrated a relation between cognitive ability performance improvement across trials. Schizophrenia cases showed less risk-taking, and earned significantly less money overall. Identifying the determinants of poor decision-making could inform interventions and possible treatments to improve their function and perhaps be of relevance to public safety if decisions are overly risky.